Analisa perpindahan panas pada dies squeeze casting - Mafruddin, Mafruddin; Iskandar, M. Nur; Irawan, Dwi (Universitas Muhammadiyah Metro, 2020)
The squeeze casting process is a metal casting process that requires a tool called extortion. Diess on casting is a component that determines checking performance. Based on this excuse, it is necessary to do a performance analysis (thermal) on squeeze casting to determine components performances. This study aims to determine the performance of the diess in squeeze casting which requires the allocation of heat that occurs and thermal efficiency diess. This research was conducted with a real experimental method with variations in testing at temperatures of 100ºC, 200ºC, 300ºC, and 400ºC using Magnesium AZ31 material and combined with aluminum. From the results of research published on the biggest thermal heater that is at a temperature of 400° C of 970.68 W with a thermal efficiency of 18%. While the heat that occurs at a temperature of 100ºC is 489.25 W and thermal efficiency is 9%, at a temperature of 200ºC is 806.28 W and thermal efficiency is 15% and at a temperature of 300ºC is 864.98 W and thermal efficiency is 16%.Keywords: Temperature, diess, squeeze casting performance.